(untitled) (Global Journal of Science Frontier Research, 2019)
Oxidation of alcohols has industrial importance as it yields several useful products Toxic and costly metal ions like Os VIII Cr VI and Ru in different oxidation states are widely used for the oxidation of a variety of organic compounds We are reporting herein the oxidation of the industrially useful primary alcohols 2-Chloroethanol 2-Butoxyethanol and 2-Phenoxyethanol using Ammonium metavanadate in acidic medium Relatively less toxic and cheaper transition metal ions of the first series are effectively used as homogeneous catalysts for the oxidation of the alcohols to the corresponding aldehydes 2-Chloroethanol is used as a precursor for ethylene oxide and is useful in the manufacture of crop protection chemicals and pharmaceuticals 2-Butoxyethanol finds use in the making of paints varnishes and industrial and household cleaners 2-Phenoxyethanol serves as a perfume fixative The oxidation is studied in the presence and absence of transition metal ions under first- order kinetic conditions concerning the inorganic oxidant The dependence of the oxidation rates of alcohols on concentrations of substrate and oxidant ionic strength and temperature is investigated From the variation of the oxidation rate with temperature the energy of activation and other thermodynamic activation parameters are evaluated and interpreted in terms of the molecular dynamics of the oxidation process The oxidation rates of the alcohols follow the sequence 2-Chloroethanol 2-Butoxyethanol 2- Phenoxyethanol which is explained based on their structural features The catalytic effect of the transition metal ions Mn II Co II and Ni II on the oxidation rates of alcohols is studied in the range M II 2 5 to 4 5 x 10-4 mol dm-3 and the sequence of catalytic efficiencies of the metal ions determined A suitable reaction mechanism is suggested for the oxidation of alcohols using Ammonium metavanadate in acidic medium